PORTUGUÊS COMO LINGUA ESTRANGEIRA: UM ESTUDO EM REPRESENTAÇÕES SOCIAIS COM CANDIDATOS AO CELPE-BRAS - Cielo, Betânia Monteiro (2014)
The main objective of this study was to analyze the social representations of the Portuguese language circulating among foreigners who were taking the CELPE-Bras test, an exam introduced by the Brazilian government to evaluate proficiency in Portuguese. Based on Serge Moscovicis psychosocial construct of social representations and complemented by Ivana Markovás dialogic perspective of this theory, we sought to analyze foreigners representations of the Portuguese language utilizing a questionnaire containing open, closed, and free association questions. The questionnaire was distributed to 95 candidates during the second edition of the 2012 CELPE-Bras exam and sought to answer the following guiding questions: 1) What are the social representations that foreigners taking the CELPE-Bras exam have of the Portuguese language? 2) Do their motivations for coming to Brazil and taking the CELPE-Bras have any impact on the social representations of the language? 3) Are the social representations influenced by the cultural matrix of the examinee? The findings indicate that the Portuguese language is seen as being beautiful, musical and difficult, and that there is a tendency to repeat the stereotyped contents held for culture to language, both among foreigners from Latin American and among those belonging to other cultural sources, regardless of their motivations.